What Constitutes a Financial System in General and the German Financial System in Particular? - Reinhard H. Schmidt; Marcel Tyrell (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2003)
This paper is one of the two introductory chapters of the book The German Financial System. It first discusses two issues that have a general bearing on the entire book, and then provides a broad overview of the German financial system. The first general issue is that of clarifying what we mean by the key term financial system and, based on this definition, of showing why the financial system of a country is important and what it might be important for. Obviously, a definition of its subject matter and an explanation of its importance are required at the outset of any book. As we will explain in Section II, we use the term financial system in a broad sense which sets it clearly apart from the narrower concept of the financial sector. The second general issue is that of how financial systems are described and analysed. Obviously, the definition of the object of analysis and the method by which the object is to be analysed are closely related to one another. The remainder of the paper provides a general overview of the German financial system. In addition, it is intended to provide a first indication of how the elements of the German financial system are related to each other, and thus to support our claim from Section II that there is indeed some merit in emphasising the systemic features of financial systems in general and of the German financial system in particular. The chapter concludes by briefly comparing the general characteristics of the German financial system with those of the financial systems of other advanced industrial countries, and taking a brief look at recent developments which might undermine the systemic character of the German financial system.
urn:nbn:de:hebis:30-17852
Keywords: 330; Finanzsystem; Finanzsektor; Finanzintermediation; Theorie; Deutschland